HIF1α regulates Mitochondrial biogenesis and Cellular senescence induced by Gamma Radiation - Bartoletti Stella, Anna <1984> (Alma Mater Studiorum - Università di Bologna, 2013)

(untitled)
Cellular response to γ-rays is mediated by ATM-p53 axis. When p53 is phosphorylated, it can transactivate several genes to induce permanent cell cycle arrest (senescence) or apoptosis. Epithelial and mesenchymal cells are more resistant to radiation-induced apoptosis and respond mainly by activating senescence. Hence, tumor cells in a senescent state might remain as “dormant” malignant in fact through disruption of p53 function, cells may overcome growth arrest. Oncocytic features were acquired in the recurring neoplasia after radiation therapy in patient with colonrectal cancer. Oncocytic tumors are characterized by aberrant biogenesis and are mainly non-aggressive neoplasms. Their low proliferation degree can be explained by chronic destabilization of HIF1α, which presides to adaptation to hypoxia and also plays a pivotal role in hypoxia-related radio-resistance. The aim of the present thesis was to verify whether mitochondrial biogenesis can be induced following radiation treatment, in relation of HIF1α status and whether is predictive of a senescence response. In this study was demonstrate that mitochondrial biogenesis parameters like mitochondrial DNA copy number could be used for the prediction of hypoxic status of tissue after radiation treatment. γ-rays induce an increase of mitochondrial mass and function, in response to a genotoxic stress that pushes cells into senescence. Mitochondrial biogenesis is only indirectly regulated by p53, whose activation triggers a MDM2-mediated HIF1α degradation, leading to the release of PGC-1β inhibition by HIF1α. On the other hand, this protein blunts the mitochondrial response to γ-rays as well as the induction of p21-mediated cell senescence, indicating prevalence of the hypoxic over the genotoxic response. Finally in vivo, post-radiotherapy mtDNA copy number increase well correlates with lack of HIF1α increase in the tissue, concluding this may be a useful molecular tool to infer the trigger of a hypoxic response during radiotherapy, which may lead to failure of activation of senescence.